PHARMACOLOGICAL EFFECT OF POLYSORBATE 80 IN CANCER CHEMOTHERAPY - Beeba, J.; Anwar, F.; Susheel, S. (International Journal of Current Pharmaceutical Research, 2014)
Objective: Tween 80 (Polysorbate 80) is a classical non-ionic surface-active detergent. It is widely used as an additive in pharmaceuticals and in the food industry.Â Many of the Tweens are considered to be carcinogens. Here in this study an attempt was made to find out whether the tween 80Â  used as an excipient in an anti cancer drug, Methotrexate affected its therapuetic efficiency or not. Methods: Hepatocellularcarcinogenesis (HCC) was induced in the wister rats by the administration of a single dose chemical carcinogen DENA (150 mg/kg i. p.). The animals exposed to DENA were treated with pure Methotrexate (MTX) and marketed MTX (0.14mg/kg by oral route through force feeding) and Tween 80 (0.14mg/kg by p. o.). Result: Exposure of DENA and Tween 80 elevated the levels of SGOT, SGPT, ALP, and AFP in Wistar rats. Histopathological examinations of the liver tissue showed marked carcinogenicity of the chemical carcinogen and excipients, while pure MTX treated group showed normal liver cell architecture. Conclusion: The study revealed that the excipient polysorbate 80 used in the marketed formulation of Methotrexate decreased the efficacy of theÂ  pure drug (pure Methotrexate).